Biodiesel production from Kutkura (Meyna spinosa Roxb. Ex.) fruit seed oil: Its characterization and engine performance evaluation with 10% and 20% blends. (1st August 2016) - Kakati, J.; Gogoi, T.K.
Highlights: Biodiesel is produced from Kutkura seed oil and its fatty acid composition is determined. Important fuel properties of biodiesel derived from Kutkura seed oil are evaluated. Properties of Kutkura seed oil and biodiesel are compared with other tree seed biodiesels. Engine performance of 10% (B10) and 20% (B20) blending of Kutkura biodiesel is reported. B10 and B20 showed better performance than conventional diesel fuel. Abstract: Kutkura ( Meyna spinosa Roxb.) is a plant species in the genus Meyna from the Rubiaceae family. Kutkura fruits are food items; the fruits and the leaves of the Kutkura plant are also used in traditional medicine. In this article, biodiesel produced from Kutkura fruit seed oil is characterized and compared with other tree seed based biodiesels. Oil content in Kutkura fruit seed was found 35.45%. Free fatty acid (FFA) content in the oil was 3.1%, hence base catalyzed transesterification was used directly for biodiesel production from Kutkura fruit seed oil. Kutkura fruit seed oil contained 7.187% palmitic, 5.382% stearic, 30.251% oleic and 52.553% linoleic acid. Calorific value, kinematic viscosity and density of Kutkura fruit seed oil were found 38.169 MJ/kg, 28.92 mm 2 /s and 922.5 kg/m 3 respectively. However, after transesterification, these properties improved to 39.717 MJ/kg, 5.601 mm 2 /s and 885.3 kg/m 3 respectively in case of the Kutkura fatty acid methyl ester (FAME). Apart from water content, all other properties of Kutkura FAME met the ASTMD6751 andEN14214 standards. Blending of Kutkura FAME with diesel up to 20% (vol.) however reduced water content down to an acceptable level of 0.038 wt.%. The kinematic viscosity also reduced to the level of conventional diesel after blending. Further, an engine performance study with biodiesel blends (B10 and B20) showed almost similar fuel consumption rate with diesel. Engine brake thermal efficiency (BTE) was more while the smoke emission was less with B10 and B20. Thus, Kutkura fruit seed is a potential source of biodiesel and blends of Kutkura FAME up to 20% can be used for realizing better performance from the engine.